The Sheik Leadership Model: An AI-Informed, Patience-Centered Framework for Sustainable Leadership in Higher Education - S.H. Sheik Mohamed; Nirmala.M; G.C. Premnivas (Asosiasi Dosen Muda Indonesia, 2026)
Leadership in higher education increasingly operates within complex governance structures marked by ethical accountability, emotional pressures, and long-term institutional responsibility. While prevailing leadership theories emphasize vision, service orientation, and moral conduct, patience remains underdeveloped as a core leadership construct. This study proposes the Sheik Leadership Model (SLM), an AI-informed, patience-centered leadership framework designed to explain sustainable leadership practices in higher education. Drawing on secondary literature and AI-assisted conceptual synthesis, the model reconceptualizes patience as an active regulatory mechanism that stabilizes ethical governance, emotional intelligence, mentorship effectiveness, and long-term institutional vision. Adopting a qualitative, conceptual research design, the study further enhances theoretical rigor through simple mathematical representation, illustrating patience as both a stabilizing multiplier and a threshold condition distinguishing reactive from sustainable leadership. The study contributes to leadership theory by positioning patience as a foundational mediator that supports decision-making consistency, institutional trust, and long-term sustainability in higher education leadership.